Piecewise Structural Equation Modeling of the Quantity Implicature in Child Language. (March 2023) - Grinstead, John; Ortiz-Ramírez, Pedro; Carreto-Guadarrama, Ximena; Arrieta-Zamudio, Ana; Pratt, Amy; Cantú-Sánchez, Myriam; Lefcheck, Jonathan; Melamed, David
We review an array of experimental methodological factors that either contribute to or detract from the measurement of pragmatic implicatures in child language. We carry out a truth value judgment task to measure children's interpretations of the Spanish existential quantifier algunos in implicature-consistent and implicature-inconsistent contexts. Independently, we take measures of children's inhibition, working memory, attention, approximate number ability, phrasal syntax, and lexicon. We model the interplay of these variables using a piecewise structural equation model (SEM), common in the life sciences, but not in the social and behavioral sciences. By 6 years of age, the children in our sample were not statistically different from adults in their interpretations. Syntax, lexicon, and inhibition significantly predict implicature generation, each accounting for unique variance. The approximate number system and inhibition significantly predict lexical development. The statistical power of the piecewise SEM components, with a sample of 64 children, is high, in comparison to a traditional, globally estimated SEM of the same data.